Unusual Reductive Cyclization of 3-Nitro-4-(phenylamino)benzoic acid: Benzimidazole instead of Phenazine - Abramovich, Maxim; Pyatnitsev, Mikhail; Tafeenko, Victor; Berezina, Anna; Zyk, Nikolai; Beloglazkina, Elena; Barskaya, Elena (Synthesis, 2025)
It is known that o-nitroanilines undergo cyclization to form phenazines in the presence of sodium borohydride under basic conditions. We have shown that under similar conditions, 3-nitro-4-(phenylamino)benzoic acid 1a cyclizes to 2-alkyl-1-phenylbenzimidazole-5-carboxylic acids. 2-Methyl-substituted benzimidazole crystallizes to form crystals of its mixed salts with NaCl and HCl, as characterized by X-ray data. Sodium alkoxide acts as a reducing agent for the nitro group of the initial o-nitroaniline in the reaction. Based on the obtained results, a possible reaction mechanism has been proposed.
Keywords: Phenazine; Benzimidazole; Borohydride reduction; Heterocycles; Ring closure